Floating Drug Delivery System: An Outlook: Floating Drug Delivery System: An Outlook - Barakoti, Himal (International Journal of Pharmaceutical & Biological Archive, 2020)
Floating drug delivery approach uses low-density systems that have sufficient buoyancy to flow over the gastric contents and remains buoyant in the stomach without affecting the stomachic emptying rate for a chronic period of time. This result is increased gastric retention time and better control of the fluctuations in plasma drug concentration with a low risk of toxicity. Drugs, which are locally active in the stomach, drugs having narrow absorption window and unstable in the intestine, and colonic environment, are the potential drug candidates. The approach not only improves drug absorption but also minimizes the mucosal irritation of drugs. As the approach requires a high fluid level in the stomach to float and work efficiently, it makes the approach limited up to some extent. Many buoyant systems have been developed based on granules, powders, capsules, tablets, laminated films, and hollow microspheres and few formulations have been commercialized in the market at the present time. This review gives an overview of the approach of floating drug delivery at present with sequential demystification thus enabling a greater understanding of their role in medicine and drug delivery